2007
DOI: 10.1002/elps.200700291
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration of a heteroconjugated imidazole–acetate complex in ACN

Abstract: ACN is an extremely poor hydrogen bond donor and therefore the anions dissolved in it are solvated mainly by other hydrogen bond donors (e.g. uncharged acids) possibly present in the solution. Under properly selected experimental conditions stabilization via hydrogen bonding can be used for separation in CE as has been demonstrated for uncharged acids by several authors. Electromigration based on heteroconjugation can be of importance, e.g. when aqueous separation medium cannot be used due to stability reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Concerning ion‐pair, it is caused by the interaction of two ions with opposite charge. Heteroconjugation and homoconjugation are the main effects in ACN, in that ACN is a dipolar‐aprotic solvent and it cannot donate hydrogen bond 30. Therefore, anions in ACN must be solvated by other hydrogen bond donor, which causes the formation of homoconjugation and heteroconjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning ion‐pair, it is caused by the interaction of two ions with opposite charge. Heteroconjugation and homoconjugation are the main effects in ACN, in that ACN is a dipolar‐aprotic solvent and it cannot donate hydrogen bond 30. Therefore, anions in ACN must be solvated by other hydrogen bond donor, which causes the formation of homoconjugation and heteroconjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Porras and Jussila studied the electromigration of heteroconjugated complexes in ACN, using imidazole as the uncharged compound and acetate as small complexing anion 40. Ma et al demonstrated that the separation of four calix[4]pyrrole derivatives in NACE was possible as a result of heteroconjugation with chloride anion 36, 37.…”
Section: Chemical Features Of Nacementioning
confidence: 99%
“…The ionic strength of the solution is not changed, because for each reacting anion A − another anion is formed. Note that non‐ionic analytes can be transformed into ionic heteroconjugates (with the constituents of the BGE), a reaction that can be used to separate initially neutral analytes by CE 31–34.…”
Section: Organic Solvents In Czementioning
confidence: 99%
“… One is the utilisation of heteroconjugation, which is hardly occurring in aqueous solution because of the excellent solvation properties of water. In solvents with low solvation ability, heterconjugation can be introduced as a vehicle to generate additional separation selectivity, and even to implement electrophoretic movement of initially non‐charged analytes 31–34. A convincing example was given by Okada (Fig.…”
Section: Conclusion: Explicit Advantages Of Organic Solventsmentioning
confidence: 99%